P‐61: Size‐Dependence Characterization of GaN‐Based Green MicroLED. Issue 1 (28th June 2021) - Zhanghu, Mengyuan; Feng, Yang; Liu, Zhaojun
Abstract : GaN‐based light‐emitting diode (LED) arrays are a promising technology in a wide range of applications. Research on size dependence performance is important in GaN‐based LED. In this paper, we study the electrical properties of 100µm, 150µm, and 200µm devices. The ideal factor is calculated by measuring the current density‐voltage characteristics to study the carrier transport mechanism. It is found that the forward low bias voltage part is mainly composed of recombination current and diffusion current. The current density in the high bias voltage part depends on the current crowding effect. The temperature variation study proves that the ideal factor has no size dependence. Besides, the electroluminescence (EL) spectrum is studied to understand size dependence in GaN internal structure. As the size decreases, the quantum confinement Stark effect (QCSE) will be suppressed, which is proved by the relationship between optical power and turn‐on voltage. These studies indicate that the application of Micro‐LED and even smaller‐sized Micro‐LEDs has unlimited possibilities and broad prospects.